Advocacy and Protection for Victims of Sexual Violence against Children: Insight from Indonesia's Experience - Krismawati, Selviana; Pratiwi, Salsabila Yumna; Smith, Nucharee Nuchkoom; Smith, Robert Brian (Universitas Negeri Semarang, 2023)
This research conducts a comprehensive exploration of the nuanced dimensions surrounding the role and protection of victims of sexual violence against children in Indonesia, with a specific focus on Decision Number 28/Pid.Sus/2021/PN Bbs, employing a normative juridical methodology. The study aims to reveal legal intricacies in victim form and protection throughout the judicial proceedings outlined in Decision Number 28/Pid.Sus/2021/PN Bbs, utilizing secondary sources such as laws, regulations, books, legal journal articles, and media coverage. Employing a descriptive analytical approach, the research identifies two pivotal dimensions. Firstly, victims of sexual violence against children in Decision Number 28/Pid.Sus/2021/PN Bbs exhibit vulnerability, easily persuadable traits, and compromised mental and physical conditions. External factors, including determinants of life, personality, and education, further contribute to the complexity of their roles. Secondly, an exploration of victim protection within the decision reveals that not all legally stipulated safeguards are embraced, with the Witness and Victim Protection Agency (LPSK) providing no support due to a lack of initiative from the family or law enforcement officials. Despite this, non-juridical protections, particularly in health, were identified, such as post-mortem medical treatment. To enhance comprehensiveness, the study incorporates perspectives of advocacy and victim protection, critically examining the efficacy of advocacy initiatives and evaluating existing frameworks for both juridical and non-juridical protection. This comprehensive approach aims to provide a holistic understanding of challenges and opportunities in safeguarding victims of sexual violence against children within the context of Decision Number 28/Pid.Sus/2021/PN Bbs.